Trasformazioni geometriche e figure dell'architettura L'Architectura Obliqua di Juan Caramuel de Lobkowitz - Iurilli, Stefania (Premio Ricerca «Città di Firenze», 2014)
The volume examines a controversial architectural treatise written at the end of the 17th century by the Spanish mathematician and polygrapher Juan Caramuel de Lobkowitz. The work, entitled Architectura Civil Recta y Obliqua, is often remembered by historians in relation to the debate that binds its author to an illustrious project: that of the Berninian colonnade in St. Peter's square. The goal of the research is to highlight, through direct and systematic reading of the work and its unusual drawings, the contributions that Caramuel had the opportunity to draw from the geometric and mathematical research of his time, in a sort of anastylosis of the Caramelian aesthetic, allowing a rigorous reading of his peculiar designed architectures.